1993
DOI: 10.1037/0882-7974.8.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant eyeblink and heart rate classical conditioning in young, middle-aged, and elderly human subjects.

Abstract: Pavlovian heart rate (HR) and eyeblink (EB) conditioning were assessed in 4 groups of Ss who differed in age: young = 19-33 years, young middle-aged = 35-48 years, old middle-aged = 50-63 years, and old = 66-78 years. A 100-ms corneal airpuff was the unconditioned stimulus and a 600-ms tone was the conditioned stimulus. A nonassociative control group received explicitly unpaired tone and airpuff presentations. All Ss were studied for 2 100-trial sessions separated by approximately 7 days. An impairment in acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 34 publications
(88 reference statements)
4
30
0
Order By: Relevance
“…Lowered responsivity to predictable aversive external stimulation, regardless of whether it is a conditioned or unconditioned stimulus, may be a characteristic of PTSD in combat veterans. These results are thus similar to the well-known findings that simple delay EB conditioning is lowered in normal elderly subjects (Durkin, Prescott, Furchtgott, Cantor, & Powell, 1993;Woodruff-Pak, Chi, Li, Pak, & Fanelli, 1997), and patients with Chronic Fatigue Syndrome (Servatius et al, 1998) or Major Depressive Disorder (Greer, Trivedi, & Thompson, 2005). The magnitude of the EB UR has been shown to be highly predictive of acquisition of simple delay EB CR, even though failure to acquire the EB CR was not associated with lowering of autonomic arousal (Flaten & Friborg, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Lowered responsivity to predictable aversive external stimulation, regardless of whether it is a conditioned or unconditioned stimulus, may be a characteristic of PTSD in combat veterans. These results are thus similar to the well-known findings that simple delay EB conditioning is lowered in normal elderly subjects (Durkin, Prescott, Furchtgott, Cantor, & Powell, 1993;Woodruff-Pak, Chi, Li, Pak, & Fanelli, 1997), and patients with Chronic Fatigue Syndrome (Servatius et al, 1998) or Major Depressive Disorder (Greer, Trivedi, & Thompson, 2005). The magnitude of the EB UR has been shown to be highly predictive of acquisition of simple delay EB CR, even though failure to acquire the EB CR was not associated with lowering of autonomic arousal (Flaten & Friborg, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Although a 500-ms interstimulus interval is not optimal for autonomic conditioning, Durkin et al (49) have shown that significant heart rate conditioning does occur using stimuli and timing parameters similar to those employed in the current experiment. Thus, it is possible that some of the areas that were significantly activated on the paired day relative to the unpaired day represent synaptic activity related to autonomic rather than somatomotor conditioning.…”
Section: Neurobiology: Logan and Grafton 7504mentioning
confidence: 95%
“…However, these studies failed to account for age-related changes in overall arousability and habituation across the groups, which were also reported (see Powell, 1999, for further discussion). A more recent study (Durkin et al, 1993) found age-associated impairments in discriminative heart-rate conditioning when nonassociative factors were controlled. Aging studies in nonhuman mammals have shown mixed results.…”
mentioning
confidence: 99%